Die Hand des Künstlers. - Gohr, Siegfried (Köln : Museum Ludwig, 1991)
Baselitz, Georg ; Bourgeois, Louise ; Broodthaers, Marcel ; Chillida, Eduardo ; Höckelmann, Antonius ; Hofmann, Hans ; Immendorff, Jörg ; Jorn, Asger ; Kelly, Ellsworth ; Kirkeby, Per ; Léger, Fernand ; Lüpertz, Markus ; Miro, Joan ; Penck, A.R. ; Picasso, Pablo ; Polke, Sigmar ; Rainer, Arnulf ; Rodin, Auguste ; Twombly, Cy ; Urteil, Andreas
Die Hand des Künstlers, Museum Ludwig, Köln, 27. april bis 23. Juni 1991
boek